Synthesis of Tungsten Carbide Nanoparticles by Reflux Reaction - Chopra, Raj kumar (My University, 2009)
Tungsten Carbide (WC) is one of the hardest material used in cutting tool industry and also as a coating material. Fine and uniform distribution of tungsten carbide in the ductile metal matrix can give remarkable results like longer tool life. By reduction in size from micro to nano scale materials show different properties because of the high surface to volume ratio. High hardness and better toughness can be obtained by synthesizing particles of tungsten carbide in nano dimensions. Nano-grained WC/Co composites have the potential to become the new materials for tools and dies and wear parts. Shorter sintering time, high purity, and precise control of composition are the benefits of nano-grained WC/Co particles. These materials have superior properties with more homogeneous microstructure than conventional WC/Co composites. Higher toughness and ductility can be achieved without reducing hardness and wear resistance. In the present investigation thermo-chemical route using reflux action technique for the synthesis of tungsten carbide nano particles has been adopted. The synthesized powder is characterized by X-Ray diffraction and TEM technique. The detail of the synthesis and characterization work is presented in this thesis. During design of experiments several failure occurred which could not give desired results. In this work only those experiments are reported which could deliver the desired results.
Keywords: Tungsten Carbide; Reflux Reaction